KOMUNIKASI ANTAR BUDAYA ANTARA MAHASISWA BATAK DAN MAHASISWA SUNDA UNIVERSITAS PADJADJARAN - Sitorus, Ronny; Dirgantara, Pradipta (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
Intercultural communication is inevitable when entering the continuity of student life. Students from various ethnicities gather in one place to gain knowledge at the University. Padjadjaran University is one of the most popular universities in Indonesia. This study aims to determine how the intercultural communication between Sundanese and Batak ethnic students at Padjadjaran University. The theory used in this research is the process of intercultural communication and barriers to intercultural communication. This study uses a qualitative method. This study uses a phenomenological approach. The subjects in this study were 2 ethnic Sundanese students and 2 ethnic Sundanese students from Padjadjaran University and the object of this research was how the process of intercultural communication was and what were the barriers to intercultural communication. This study uses a collection technique, semi-structured in-depth interview. The results of this study show that intercultural communication of language is an important thing for the process of intercultural communication because the language itself is also an obstacle when conducting intercultural communication where students of ethnic Sundanese have difficulty regarding the Batak language on the other hand, ethnic Batak students have difficulties regarding the Sundanese language.